Poly(ADP-ribose) polymerase 1 participates in the phase entrainment of circadian clocks to feeding - Asher, Gad; Reinke, Hans; Altmeyer, Matthias; Gutierrez-Arcelus, Maria; Hottiger, Michael O; Schibler, Ueli (Cell, 2010)
Circadian clocks in peripheral organs are tightly coupled to cellular metabolism and are readily entrained by feeding-fasting cycles. However, the molecular mechanisms involved are largely unknown. Here we show that in liver the activity of PARP-1, an NAD(+)-dependent ADP-ribosyltransferase, oscillates in a daily manner and is regulated by feeding. We provide biochemical evidence that PARP-1 binds and poly(ADP-ribosyl)ates CLOCK at the beginning of the light phase. The loss of PARP-1 enhances the binding of CLOCK-BMAL1 to DNA and leads to a phase-shift of the interaction of CLOCK-BMAL1 with PER and CRY repressor proteins. As a consequence, CLOCK-BMAL1-dependent gene expression is altered in PARP-1-deficient mice, in particular in response to changes in feeding times. Our results show that Parp-1 knockout mice exhibit impaired food entrainment of peripheral circadian clocks and support a role for PARP-1 in connecting feeding with the mammalian timing system.